The Impact of Environmental Conditions on Player Loads During Preseason Training Sessions in Women's Soccer Athletes. Issue 10 (October 2021) - Austin, Alexis B.; Collins, Sean M.; Huggins, Robert A.; Smith, Brittany A.; Bowman, Thomas G.
Abstract : Abstract: Austin, AB, Collins, SM, Huggins, RA, Smith, BA, and Bowman, TG. The impact of environmental conditions on player loads during preseason training sessions in women's soccer athletes. J Strength Cond Res 35(10): 2775–2782, 2021—Our objective was to determine the impact of environmental conditions on player loads during preseason training sessions in women's soccer athletes. Eleven women's NCAA Division III soccer players (age = 20 ± 1 year, height = 167.28 ± 8.65 cm, body mass = 60.18 ± 5.42 kg, V[Combining Dot Above]O2 max = 43.70 ± 3.95 ml·kg −1 ·min −1 ) volunteered to wear Global Positioning System (GPS) devices (Sports Performance Tracking, Melbourne, Australia) that provided measures of training session external intensity throughout all preseason practices ( n = 15). We recorded wet-bulb globe temperature (WBGT), session Rating of Perceived Exertion-Training Load (sRPE-TL), and ΔBM during each preseason training session and set α ⩽ 0.05. The combination of WBGT, sRPE-TL, and ΔBM explained 34% of the variance in GPS-based intensity score (proprietary measure) ( F 3, 153 = 26.25, p < 0.001). Wet-bulb globe temperature ( t 156 = −2.58, p = 0.01), sRPE ( t 156 = 8.24, p < 0.001), and ΔBM ( t 156 = 2.39, p = 0.02) were significantly associated with intensity. The ΔBM from prepractice (60.00 ± 5.21 kg) to postpractice (59.61 ± 5.10 kg) was statistically significant ( p < 0.001); however, ΔBM from the beginning of preseason (59.87 ± 5.31 kg) to the end of preseason (59.91 ± 5.58 kg) was not significant ( p = 0.89). Despite relatively low to moderate environmental conditions, increases in WBGT were associated with reductions in GPS intensity and elevated internal load via sRPE-TL. Our findings support the association between exercise intensity and WBGT, internal load, and hydration status; thus, coaches and exercise scientists should take these factors into account when monitoring or interpreting intensity metrics. Furthermore, these findings support the continued use of environmental monitoring and hydration best-practice policies to limit exercise intensity in the heat so as to mitigate excessive heat stress.